Investing in sports stocks : a case of Sportfolio Management Inc. - Chard, Chris (SAGE Knowledge. Cases., 2017)
Jordan Bourne is the Chief Executive Officer (CEO) of Sportfolio Management Inc. (SMI), a small hedge fund operating out of Boston, Mass. SMI provides prudent and profitable investment management services to clients through active investment in publicly traded companies operating in sport-related business endeavors. By employing both "long" and "short" investment management strategies, Bourne's objective is to achieve a positive rate of return in the Sportfolio for her valued clients. Assistance from the firm's Investment Analysts is vital to meet this objective.